Delphi method of developing environmental well-being indicators for the evaluation of urban sustainability in Malaysia - Musa, Haruna Danladi; Yacob, Mohd Rusli; Abdullah, Ahmad Makmom; Ishak, Mohd Yusoff (Elsevier, 2015)
Urban sustainability is the goal of many cities to improve well-being of urban residents that live in cities. This study sought expert consensus in a 2-round Delphi survey to rate the importance of environmental well-being indicators to assess urban sustainability. A multidisciplinary group of 45 experts rated the importance of 18 indicators with response rates of 75.6% and 91.2% in the rounds. Consensus was reached on 12 indicators with a high level of group agreement (Kendall's W=0.522,P < 0.001), and high correlation in rounds rankings (rho:0. 964, p>0.01)